Gestión de recursos humanos en la Ferretería Colombatti: estrategias para mejorar el desempeño y la retención del personal, periodo 2023. - Gavidia Mancilla, Luis Eduardo (2024)
In the contemporary business context, human resource management has become a crucial factor for organizational success. This study analyzes how human resource management influences the performance and retention of staff at Colombatti Hardware Store, located in Babahoyo. The research evaluates processes such as personnel selection and hiring, training and development, performance management, and retention policies. By exploring these components, it aims to establish a relationship between the quality of human resource management and staff performance and retention levels. The results will provide effective strategies to maximize performance, improve the work environment, and promote the company's sustainability and competitiveness. Additionally, this analysis will offer valuable insights applicable to other organizations in similar sectors.